Vertebral Body Tethering in AIS Management-A Preliminary Report - Aurélien Courvoisier; Alice Baroncini; Clément Jeandel; Clémentine Barra; Yan Lefevre; Federico Solla; Richard Gouron; Jean-Damien Métaizeau; Marie-Christine Maximin; Vincent Cunin (MDPI AG, 2023)
Vertebral Body Tethering (VBT) is a recently developed surgical technique for the treatment of progressive and severe scoliosis in patients with significant growth potential. It has been used since the first exploratory series, which showed encouraging results on the progressive correction of the major curves. This study reports on a retrospective series of 85 patients extracted from a French cohort, with a follow-up at a minimum of two years after a VBT with recent screws-and-tether constructs. The major and compensatory curves were measured pre-operatively, at the 1st standing X-ray, at 1 year, and at the last available follow-up. The complications were also analyzed. A significant improvement was observed in the curve magnitude after surgery. Thanks to growth modulation, both the main and the secondary curves continued to progress over time. Both the thoracic kyphosis and lumbar lordosis remained stable over time. Overcorrection occurred in 11% of the cases. Tether breakage was observed in 2% of the cases and pulmonary complications in 3% of the cases. VBT is an effective technique for the management of adolescent idiopathic scoliosis patients with residual growth potential. VBT opens an era of a more subtle and patient-specific surgical management of AIS that considers parameters such as flexibility and growth.